SREHA: An Efficient Handover Authentication Scheme Based on Social Relationships in Mobile Edge Computing - Ziwang Wang; Liang Wang; Huili Yan; Zhize Wu (IEEE Access, 2024)
Handover authentication in mobile scenarios refers to the process of re-authentication when a mobile device switches from one edge server to another. However, existing handover authentication schemes fail to optimize handover latency, security, and energy consumption comprehensively. To ensure continuity, security, and lightweight operation during switching, we propose SREHA, an efficient handover authentication scheme based on social relationships. First, the edge server builds its own social circle through bidirectional identity and integrity authentication, saving the social relationships in the public blockchain. Second, when the mobile device performs handover authentication, it evaluates the trustworthiness of the target node based on the social relationships of the current edge server node and filters the nodes that satisfy the trustworthiness criteria. By transferring the authentication load to the server side, SREHA prevents the device from expending significant resources to maintain reputation and authentication information, thereby achieving a lightweight handover authentication process. Third, we propose a malicious node detection model based on heuristic algorithms, which enhances the security of the handover authentication-free framework. Lastly, we implement a prototype of the proposed scheme and validate its security using the Scyther formal validation tool. The results demonstrate that our scheme effectively reduces the time delay of the handover authentication process, and exhibits lower computational overhead and higher security compared to existing schemes.